2015
DOI: 10.1007/s11136-015-1070-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among symptom severity, coping styles, and quality of life in community-dwelling women with urinary incontinence: a multiple mediator model

Abstract: The use of avoidant and palliative coping styles was higher with more severe urine leakage, and QOL tended to be poorer. Coping styles should be addressed in UI management. It may be of particular value to look closely at negative coping styles and implement education and training of patients in improving their coping skills related to managing UI, which will in turn improve their QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(48 reference statements)
0
7
1
Order By: Relevance
“…In spite of the literature pointing out that UI leads to restrictions in social participation in our study participation was not a domain in which disability scores were significantly different between incontinent and nonincontinent women. In a study with older incontinent Australian women, the authors found an association between UI and social dysfunction, but they pointed out that this association is not casual; in fact, it is a reflection of general health and overall functioning level of women, exploring a new axis of discussion about this domain and approaching the influence of environmental aspects on it.…”
Section: Discussioncontrasting
confidence: 93%
“…In spite of the literature pointing out that UI leads to restrictions in social participation in our study participation was not a domain in which disability scores were significantly different between incontinent and nonincontinent women. In a study with older incontinent Australian women, the authors found an association between UI and social dysfunction, but they pointed out that this association is not casual; in fact, it is a reflection of general health and overall functioning level of women, exploring a new axis of discussion about this domain and approaching the influence of environmental aspects on it.…”
Section: Discussioncontrasting
confidence: 93%
“…34 This negative association of UI with HRQoL and mental health is in accordance with worldwide studies such as EpiLUTS 5 as well as studies from Asia. [9][10][11][12][13][14][15][16][17][18] MUI in particular is generally reported as being the most detrimental to HRQoL/mental health while SUI is associated with the least impairment. [10][11][12]14,17 The unpredictability of UUI has been suggested as a major factor for a poorer QoL with MUI and UUI, as those with SUI may be better able to adapt their lifestyle and avoid situations (such as heavy lifting or exercising) that lead to involuntary loss of urine.…”
Section: T a B L E 4 Participant Satisfaction With Any Treatmentmentioning
confidence: 99%
“…5 In an analysis of the National Social Life, Health and Aging Project undertaken in US adults from 2010 to 2011, UI was one of the most significant contributors to poor mental health for women. 8 A number of studies undertaken in Asia have also demonstrated the negative association of UI with health-related quality of life (HRQoL)/mental health, [9][10][11][12][13][14][15][16][17][18] reporting a substantial impact that can be similar to or greater than that caused by other chronic medical diseases, such as diabetes, hyperlipidemia, and chronic kidney disease. 13,19 Despite this, a large proportion of individuals with UI do not seek treatment for their symptoms 20,21 and of those who receive pharmacotherapy, many are dissatisfied and discontinue medication.…”
mentioning
confidence: 99%
“…This variation between studies may be related to different definitions of UI, different methodologies for data collection, or the differences in the demographics of the study populations (6). UI significantly limits the lives of women affected due to the physical, psychological, and social inconveniences (7). The fear of leakage and odor may be related to embarrassment, frustration, depressive mood, psychological distress, and social isolation (8,9).…”
Section: Introductionmentioning
confidence: 99%